Corruption and Financial Development: Evidence from Eastern Europe and Central Asia Countries - Ekşi, Ibrahim Halil; Doğan, Berna (Public Finance Quarterly, 2020)
Studying the relation between corruption perception and financial markets and examining its consequences for the financial system have attracted many researchers in recent years. To understand the effect of it’s to financial markets is important for especially emerging countries. This paper examined the impact of Corruption Perception Index (CPI), government size, openness, and GDP on the financial development using the Generalized Method of Moment (GMM) approach of 19 Eastern Europe and Central Asia countries for the period 2012 to 2017 as yearly dates. Our findings suggest that there is not a relationship between the level of corruption perception and financial development.